Gaps in Medical Students' Competencies to Deal With Intimate Partner Violence in Key Mozambican Medical Schools - Beatriz Manuel; Beatriz Manuel; Kristien Roelens; Armindo Tiago; Ines Keygnaert; Martin Valcke (Frontiers Media S.A., 2019)
Purpose: The researchers aimed to identify the gaps in competencies designed to help medical students to deal with Intimate Partner Violence (IPV) in key Mozambican medical schools curricula.Method: A survey was administered to 3rd and 6th-year medical students (N387), enrolled in five medical schools in Mozambique. The instrument focused on mapping students' perceived mastery of their knowledge, skills, and attitudes related to IPV.Results: In total, 387 medical students (RR 66%) participated in the survey. The overall mean perceived mastery of IPV competence was 36.18 (SD = 24.52) for knowledge, 32.01 (SD = 27.37) for skills, and 43.47 (SD = 27.58) for attitudes. Though 6th-year students reported a significantly higher mastery level, it is still below a mastery-learning benchmark of 80%.Conclusions: Medical students report critically low levels in their mastery of IPV- related competencies. This implies a need for a more comprehensive approach to developing knowledge, skills, and attitudes to deal with the victims of IPV.